2021
DOI: 10.1111/bph.15525
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the signalling, structure and function of the 20‐HETE‐GPR75 pairing: Identifying the chemokine CCL5 as a negative regulator of GPR75

Abstract: Background and Purpose: The G-protein-coupled receptor GPR75 (Gq) and its ligand, the cytochrome P450-derived vasoactive eicosanoid 20-hydroxyeicosatetraenoic acid (20-HETE), are involved in the activation of pro-inflammatory and hypertensive signalling cascades contributing to diabetes, obesity, vascular dysfunction/remodelling, hypertension and cardiovascular disease. Little is known as to how, where and with what affinity 20-HETE interacts with GPR75. Experimental Approach: To better understand the pairing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…That this sensitization to constrictor stimuli was 20-HETE-dependent is evident by the ability of its receptor blocker, AAA, to prevent the increased contraction to phenylephrine. We have shown that 20-HETE-GPR75 pairing results in a rapid increase in intracellular calcium and that AAA blocks the binding/pairing and the ensuing signaling cascade [3,4]. Hence, it is reasonable to suggest that in these mice, the vascular smooth muscle 20-HETE-GPR75 -signaling pathway is amplified leading to increasing intracellular calcium via mechanisms that may include inhibition of BK Ca 2þ channels and activation of L-type Ca þ2 channels and/or activation of the ROCK leading to increased phosphorylation of MLC [12,13,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That this sensitization to constrictor stimuli was 20-HETE-dependent is evident by the ability of its receptor blocker, AAA, to prevent the increased contraction to phenylephrine. We have shown that 20-HETE-GPR75 pairing results in a rapid increase in intracellular calcium and that AAA blocks the binding/pairing and the ensuing signaling cascade [3,4]. Hence, it is reasonable to suggest that in these mice, the vascular smooth muscle 20-HETE-GPR75 -signaling pathway is amplified leading to increasing intracellular calcium via mechanisms that may include inhibition of BK Ca 2þ channels and activation of L-type Ca þ2 channels and/or activation of the ROCK leading to increased phosphorylation of MLC [12,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Both male and female mice were used in this study as they exhibited similar phenotypic changes with respect to Cyp4a12 overexpression, blood pressure and vascular function and remodeling. A water-soluble 20-HETE receptor antagonist, N-disodium succinate-20-hydroxyeicosa-6(Z),15(Z)-diencarboxamide (AAA), was used to assess the contribution of 20-HETE to the phenotype of these mice [4,38,39]. AAA was administered to the mice, via the drinking water (vehicle), at a dose of 10 mg/kg/day.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…20-HETE can activate nuclear factor-kappa B (NF-κB) and stimulate the production of inflammatory cytokines in human endothelial cells (Ishizuka et al, 2008). Recent studies have proved that 20-HETE could bind to the G-protein coupled receptor 75 (GPR75) to promote c-Src-mediated-EGFR and trigger the downstream MAPK pathway to induce ACE expression and endothelial dysfunction in human endothelial cells (Garcia et al, 2017;Pascale et al, 2021). 20-HETE/GPR75 also triggered PI3K/ AKT pathway to promote vascular smooth muscle cells migration, hypertrophy.…”
Section: The Roles Of Cytochrome P450 ω-Hydroxylase-mediated Eicosanoids In Inflammation-associated Diseasesmentioning
confidence: 99%
“…Thus, it has been proposed that 20-HETE-GPR75 pairing may be a therapeutic target to treat cardiovascular and renal diseases in which changes in the 20-HETE formation play a role in pathogenesis. Recently, Pascale et al 30 reported that 20-HETE is a high-affinity ligand for GPR75, whereas RANTES/CCL5 is a low-affinity negative regulator of GPR75. Hence, these data raise the possibility that GPR75 plays a crucial role in the pathogenesis of septic shock.…”
Section: Introductionmentioning
confidence: 99%